Inteligencia emocional y habilidades sociales en niños de instituciones educativas del nivel inicial zona urbana ciudad de Caballococha 2022 - Perez Aimani, Geovany (2024)
Relating social skills and emotional intelligence in five-year-old students in the initial stage in three educational institutions of Caballococha was the relevant objective of the research. A relational study was carried out using a crosssectional, field and bivariate design, where 120 children were observed using observation guides validated by experts. The results revealed a high and positive relationship (Pearson correlation coefficient rxy = 0.880) between the variables studied. This finding suggests that as emotional intelligence characteristics increase, students’ social skills improve. The results of the Kolmogorov-Smirnov tests indicate that the variables of emotional intelligence and social skills do not follow a normal distribution in the sample studied. In addition, the Student’s t-test revealed a significant relationship (p<0.05) between them, confirming the hypothesis of the study and having important implications for the educational field because it underlines the need to design pedagogical interventions that foster the variables investigated in children from an early age.